Territorial Economic Impacts of Climate Anomalies in Brazil - Alexandre Porsse; Eduardo Haddad; Paula Pereda (European Regional Science Association (ERSA), 2013)
This paper evaluates the systemic impact of climate variations in a regional perspective using an interregional CGE model integrated with a physical model estimated for agriculture in order to catch the effects of climate change. The methodological approach adopted to conduct such analysis was developed in two stages. At the first stage, a profit model was estimated for the agriculture sector using econometric tools in order to obtain structural parameters for projecting the effect of climate anomalies physical on the production of agriculture sector (permanent and temporary crops). At the second stage, this projection is translated as a technological productivity shock into the CGE model to evaluate the general equilibrium effect of climate anomalies. Climate anomalies are defined as deviations of rainfalls over the historic trend and the productivity shock is computed to mimic the climate anomalies observed in 2005. The CGE model used in this study id the well documented B-MARIA model. This model recognizes the 27 Brazilian regions and the results are based on a bottom-up approach ? i.e. national results are obtained from the aggregation of regional results. The model identifies 56 production/investment sectors in each region producing 110 commodities, one representative household in each region, regional governments and one Federal government, and a single foreign area that trades with each domestic region, through a network of ports of exit and ports of entry. Three local primary factors are used in the production process, according to regional endowments (land, capital and labour). The results show that a general equilibrium approach can provide a better comprehension about the systemic impact of climate anomalies, suggesting the economic costs are higher than those that would be observed in a partial equilibrium analysis. In addition, intersectoral and interregional linkages as well price effects seem to be important transmission channels in the context of systemic impact of climate anomalies.
Keywords: Q54; R13; 330; climate anomalies; systemic impact; interregional CGE analysis